2013
DOI: 10.1002/bies.201300118
|View full text |Cite
|
Sign up to set email alerts
|

Two‐pore channels (TPCs): Current controversies

Abstract: Much excitement surrounded the proposal that a family of endo-lysosomal channels, the two-pore channels (TPCs) were the long sought after targets of the Ca(2+) -mobilising messenger, nicotinic acid adenine dinucleotide phosphate (NAADP). However, the role of TPCs in NAADP signalling may be more complex than originally envisaged. First, NAADP may not bind directly to TPCs but via an accessory protein. Second, two papers recently challenged the notion that TPCs are NAADP-regulated Ca(2+) channels by suggesting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 85 publications
(172 reference statements)
1
86
0
2
Order By: Relevance
“…The fact that NAADP-dependent Ca 2ϩ signaling is enhanced by the expression of hTPC1, hTPC2, and rTPC3, respectively, provides further support for the view that TPCs are of fundamental importance to this process (11), irrespective of the controversy surrounding their ability to conduct Ca 2ϩ (9,10,13). That hTPC1 was entirely restricted to different subpopulations of endosomes, hTPC2 to lysosomes, and rTPC3 to both endosomes and lysosomes provided us with the opportunity to further assess the capacity for organellar coupling to the ER by CICR.…”
Section: Discussionmentioning
confidence: 67%
“…The fact that NAADP-dependent Ca 2ϩ signaling is enhanced by the expression of hTPC1, hTPC2, and rTPC3, respectively, provides further support for the view that TPCs are of fundamental importance to this process (11), irrespective of the controversy surrounding their ability to conduct Ca 2ϩ (9,10,13). That hTPC1 was entirely restricted to different subpopulations of endosomes, hTPC2 to lysosomes, and rTPC3 to both endosomes and lysosomes provided us with the opportunity to further assess the capacity for organellar coupling to the ER by CICR.…”
Section: Discussionmentioning
confidence: 67%
“…There is evidence that TPC1 is mainly present in the proximal endosomal system, and TPC2 is predominantly expressed on late endosomes and lysosomes 16,18,19 . The activation mechanism of TPCs is complex and has been suggested to involve the second messenger nicotinic acid adenine dinucleotide phosphate (NAADP) and the endolysosomal membrane lipidphosphatidylinositol (3,5)bisphosphate (PI(3,5)P 2 ) 17,18,[20][21][22][23][24] . Independent of what the nature of the endogenous ligand of these channels might be, there is substantial evidence that on activation TPCs mediate the release of Ca 2 þ from lysosomal stores.…”
mentioning
confidence: 99%
“…4,10,60,[69][70][71] Soon after, TPCs were also described as PtdIns(3,5)P2-regulated Na C selective channels, 5,6 and, again, overexpression of TPCs stimulated the PI(3,5)P2-induced current, while this current was abrogated in double-KO mice lacking TPC1 and TPC2. 5,6,71 Nowadays, different molecules have been suggested as regulators of TPCs activity.…”
Section: Activity Regulationmentioning
confidence: 99%
“…4 Still, on the other hand, in 2012 and 2013 2 independent studies refuted that mammalian TPCs were Ca 2C release channels activated by NAADP, probing that they are not Ca 2C but Na C release channels that are not activated by NAADP but by phosphatidylinositol 3,5-bisphosphate (PtdIns(3,5)P2) and inhibited by the mammalian target of rapamycin (mTOR), 5,6 which caused a great commotion regarding TPCs regulation and function among the scientific community. [7][8][9][10] Nowadays, it is accepted that mammalian TPCs not only function as Ca 2C or Na C release channels, but also as H C and K C channels, 11,12 and it has been demonstrated that TPCs can be activated by other signals apart from NAADP and PI (3,5)P2, such as the leucine-rich repeat kinase 2 (LRRK2) 13 or action potentials, 14 and inhibited by Mg 2C concentrations, 15 Ca 2C and Na C ion channels inhibitors, 16,17 or c-Jun N-terminal kinase (JNK) and p38 kinase, 15 apart from mTOR. So that, it seems reasonable that, according to the cellular context, TPCs could be differentially regulated and exert different functions.…”
Section: Introductionmentioning
confidence: 99%